Maintain load test / Afiq Eqwan Azman - Azman, Afiq Eqwan (2014)
The practical training with course code BSB351 is compulsory subject that must be completed by the student of Diploma Building Survey AP119 before graduate. The purpose of practical training is to make the student an industry-ready professional. The practical training gave the real working situation so that student can apply the skills in work fields after graduate. This would be a good preparation for the student as the practical training is essential. I have applied at the Jabatan Kerja Raya Kuantan (JKR) for my practical training. The duration of my training is 18 weeks. I was placed under the Department of Building under the supervised of En Sulaiman bin Birang (Engineer Assistant). During the practical time , I was given the opportunity to do all the office work and site visit on the undergoing project under the supervise of experiences staff in the JKR. When I was exposed to this kind work it help me to inculcate commitment to work, apply all my study knowledge to practical situations, help me in technical and soft skills, get acquainted with professional work environment and develop ethical values.